Na2Si3O7/Ag micro and nano-structured glassy composites: The experimental and MCNP simulation surveys of their radiation shielding performances - Caglar, Mustafa; Karabul, Yasar; Kilic, Mehmet; Ozdemir, Zeynep Guven; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In the present work, the very low-cost glassy structured sodium silicate (Na2Si3O7) matrix has been reinforced with micro-and nano-sized silver (Ag) particles in different weight percentages. The ionizing radiation shielding performances of the micro and nano-structured composites have been determined experimentally and theoretically for the first time. The experiments have been realized by the gamma-ray spectroscopy setup equipped with NaI(Tl) detector and Ba-133 point radioactive source. The radiation shielding performance has been discussed in the context of mass attenuation coefficient (mu/rho) half-value layer (HVL), and mean free path (MFP). Besides, the theoretical research related to the radiation shielding ability of the samples has been carried out by using the Monte Carlo N-Particle Transport (MCNP) v6.2 (c) simulation code. Since the experimental values and MCNP findings are very close to each other, MCNP simulation has been extended to a large incoming photon energy interval ranging from 25 keV to 1000 keV for both micro-and nano-structured composites. The particle size effect (PSE) on radiation shielding performance has been investigated and discussed. As a result of PSE research, it has been revealed that the addition of nanoparticles is more effective in the improvement of the radiation shielding for the lowest Ag concentration and low photon energies. Additionally, the radiation shielding capability of the composites has been discussed in the context of ambient dose equivalent, H*(10) which is one of the operational quantities. By using the ambient dose equivalent definition, the ambient dose rate values of the composites have been calculated for the first time. In conclusion, it has been determined the composites with higher micro-and nano-Ag particle additives have considerably good radiation shielding ability against low energy photons that are mostly utilized in diagnostic and treatment medical applications.
Keywords: Nanocomposite; Ag particle; Mass attenuation coefficient; MCNP simulation; Ambient dose equivalent; ATTENUATION; RAYS; Nuclear Science & Technology